Drawing the Other ‘Other’: A Conversation with John Hejduk - Almaç, Bihter (Architecture Image Studies, 2023)
A Conversation from the Wild Fields of Architecture is a set of drawings that are conceived and built as a visual transcript. The imagined conversation is between John Hejduk and myself through the mechanism of his Masques and by my interventions. In this paper, I discuss the Masques of John Hejduk as representing architecture’s otherness, set alongside Michael Hays’ discussions of the Late Avant-Garde and Roland Barthes’ ideas about the creation of the new. And within this context, the conversation piece aims to greet the Masques in their peculiar way that they demand; by the blurring of authorship in an a-synchronous collaborative creative work in which the others/observers stimulate the outcome as a performance. A Conversation from the Wild Fields of Architecture is thus an experiment resides at the initial point of departure from normative architecture by meeting instead the other condition where speculation is in fact the only accurate act of engagement.